2016
DOI: 10.1016/j.drugalcdep.2016.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prescription drug monitoring programs and pill mill laws on high-risk opioid prescribers: A comparative interrupted time series analysis

Abstract: Background Prescription drug monitoring programs (PDMPs) and pill mill laws were implemented to reduce opioid-related injuries/deaths. We evaluated their effects on high-risk prescribers in Florida. Methods We used IMS Health's LRx Lifelink database between July 2010 and September 2012 to identify opioid-prescribing prescribers in Florida (intervention state, N: 38,465) and Georgia (control state, N: 18,566). The pre-intervention, intervention, and post-intervention periods were: July 2010–June 2011, July 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
117
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 100 publications
(118 citation statements)
references
References 20 publications
1
117
0
Order By: Relevance
“…Prescriber utilization has increased with the integration of PDMPs within electronic medical records, and many states now require daily reporting of data. It is therefore not surprising that early PDMP studies reported mixed findings (Rutkow et al, 2015; Islam and McRae, 2014; Ringwalt et al, 2015; Chang et al, 2016); given the varying levels of PDMP implementation and utilization by prescribers.…”
Section: Introductionmentioning
confidence: 99%
“…Prescriber utilization has increased with the integration of PDMPs within electronic medical records, and many states now require daily reporting of data. It is therefore not surprising that early PDMP studies reported mixed findings (Rutkow et al, 2015; Islam and McRae, 2014; Ringwalt et al, 2015; Chang et al, 2016); given the varying levels of PDMP implementation and utilization by prescribers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, about 80% of high‐risk prescribers remained so following policy implementation while at most 60% of high‐risk patients persisted. Similarly, we estimate larger policy effects among high‐risk patients than high‐risk prescribers at 1 year as well; for example, we estimate a 25% to 70% reduction in total opioid volume among high‐risk patients compared with a 13.5% reduction among high‐risk prescribers . Further study is necessary to evaluate these differential effects.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies suggest that these policies can reduce prescription opioid utilization and deaths . However, some studies fail to identify such impact .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we examined self-reported quantities of opioids used and not empirically determined doses, these findings may be tapping into the same underlying relationship between volatility in actual dose, tolerance, and overdose risk. Better understanding this relationship as well as any other novel overdose risk factors is particularly important in context of the evolving opioid epidemic, where opioid stewardship initiatives are constricting prescribing and the availability of diverted prescription opioids (Chang et al, 2016; Lyapustina et al, 2016; Rutkow et al, 2015) and both rates of heroin use (United Nations Office on Drugs and Crime, 2016) and deaths from synthetic opioids (Rudd, Seth, David, & Scholl, 2016) are increasing.…”
Section: Discussionmentioning
confidence: 99%